(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Medical termination of Pregnancy Act is one such Act which was brought by the Indian Government to streamline the process of abortions conducted in India. Its rules were framed for the first time in 1972, amended in 1975, 1977, 2003, and 2009 and recently in October 2014. The main motive of passing such bills was to decrease the female foeticide rate, decrease the maternal mortality rate, improve the health of the mother and the newborn and to avoid unwanted and illegal abortion practises. In spite of these measures from the government, more than 5000 deaths due to unsafe abortions take place every year in our country. The main cause of such death related to abortion is mainly due to the ignorance of the general public towards abortion. Majority of the women, not only in the rural parts, but also in the urban regions does not know about the mere existence of the MTP law. Hence this study was aimed to estimate the level of awareness about the MTP Act among the apparently healthy reproductive age group public, visiting the hospital and apart from it, we also educate them regarding the MTP Act and its uses. Among our participants the minimum age reported was 20 and the maximum age was 45. Out of total 220, female accounted to 63.2% and male 36.8%. Among them married people accounted for 69.5%, unmarried 28.2% and others were 2.3%. 42.3% of people had history of abortion their family but 64% of people doesn’t know whether the conducted abortion was a legal or a illegal one. Eleven questions were asked to the participants and an initial assessment of their knowledge was done with the help of a questionnaire. After this immediately, educational intervention was carried out about the law and after a gap period of one month the participants were asked the same questions as before using telecommunication device and their knowledge was tested.